Formula over Function? From Algorithms to Values in Judicial Evaluation - Francesco Contini; Richard Mohr; Marco Velicogna (Oñati Socio-Legal Series)
This paper discusses the forms and effects of the ‘invasion’ of the ‘temples of the law’ by new economic and managerial forms of performance evaluation. While traditional judicial evaluation focused on how to select and promote individual judges and on the legal quality of the single case, new quantitative methods and formulas are being introduced to assess efficiency, productivity and timeliness of judges and courts. Building on two case studies, from Spain and the Netherlands, the paper illustrates two contrasting approaches to judicial performance evaluation. On the one hand individual judges' productivity is evaluated through quantitative data and mathematical algorithms: in the extreme case considered here, judge's remuneration was adjusted accordingly. On the other hand quantitative and qualitative data, collected by a variety of methods and theoretical frameworks, are used as the basis of a multi-layered negotiation process designed to find a synthesis between competing economic, legal and social values aimed at improving overall organizational performance. Considering the flaws of unidimensional measurement and evaluation systems and considering the incommensurability of the results of the multiple evaluative frameworks (economic, legal, sociological) required to overcome such flaws, the authors argue there is a need for political dialogue between relevant players in order to allocate the values appropriate to judicial evaluation.